2019
DOI: 10.1097/phh.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Top Training Needs of the Governmental Public Health Workforce

Abstract: Context: Workforce development in governmental public health has historically focused on discipline-specific skills. However, as the field of public health has evolved, crosscutting skills have become critical. The 2017 fielding of the Public Health Workforce Interests and Needs Survey (PH WINS) provides a national benchmark for gaps in crosscutting skills in state and local health departments. Objective: The purpose of this article is to identify top areas of training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…All respondents answered (1) whether they felt that the item was important in their day-to-day work and (2) how they characterized their ability to perform the item. This section's restructuring is described in detail elsewhere in this supplement 16. The emerging concepts section was modified slightly,14 and a new question was added to gauge respondent perception about the appropriate role of the SHA in other sectors related to health (eg, education, transportation).…”
Section: Methodsmentioning
confidence: 99%
“…All respondents answered (1) whether they felt that the item was important in their day-to-day work and (2) how they characterized their ability to perform the item. This section's restructuring is described in detail elsewhere in this supplement 16. The emerging concepts section was modified slightly,14 and a new question was added to gauge respondent perception about the appropriate role of the SHA in other sectors related to health (eg, education, transportation).…”
Section: Methodsmentioning
confidence: 99%
“…While the first fielding of PH WINS in 2014 included items related to training needs, a reimagining of the section was deemed necessary for 2017 15. In partnership with the de Beaumont Foundation, the Association of State and Territorial Health Officials convened the PH WINS Standardized Training Needs Assessment Workgroup—cochaired by representatives from the National Association of County & City Health Officials and the National Network of Public Health Institutes—to revise the training needs section for the 2017 survey launch 20.…”
Section: Methodsmentioning
confidence: 99%
“…Training needs in public health have been studied, but primarily with a discipline-specific or agency-specific focus 7,8,11,15–19. The Public Health Workforce Interests and Needs Survey (PH WINS) was first launched in 2014 with state health agencies and a pilot of local health agencies and explored demographics, trends, workplace environment, and training needs 10.…”
mentioning
confidence: 99%
“…For individual skill building, on-thejob training opportunities in EBDM now include both in-person and distance learning modalities (9). Despite improvements in some areas, skill gaps persist (10,11). A 2017 national survey of state and local health department employees found that the highest skill gaps were in financial management, systems and strategic thinking, developing a vision for a healthy community, and change management (11).…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in some areas, skill gaps persist (10,11). A 2017 national survey of state and local health department employees found that the highest skill gaps were in financial management, systems and strategic thinking, developing a vision for a healthy community, and change management (11). It remains unknown whether employees in accredited health departments are better equipped and supported to apply EBDM skills than those in nonaccredited departments.…”
Section: Introductionmentioning
confidence: 99%